ANALISIS MINAT KUNJUNG DI PERPUSTAKAAN KANTOR PERWAKILAN BANK INDONESIA KALIMANTAN BARAT - Tara, Subikti Bagus; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background of this research was the interest in visiting the library a Representative Office of Indonesia Bank in West Kalimantan is low. The purpose is to know the level of interest in visiting the library in a Representative Office of Indonesia Bank in Kalimantan Barat. The method is qualitative method. The technique of data collecting through observation, interview, and documentation which conducted by 5 (five) interviewees. The result of research shows that the interest in visiting the library in a Representative Office in West Kalimantan is low. It is based of the report from guest in January until July in 2019.Keywords: Interest in Visiting, Indonesia Bank, Library